A new and 23 known cardenolide glycosides from Thevetia neriifolia seeds and their cytotoxic activities against human oral carcinoma cell lines. Issue 22 (18th November 2021) - Tatsuno, Satoru; Iguchi, Tomoki; Kuroda, Minpei; Ishihara, Mai; Sakagami, Hiroshi; Mimaki, Yoshihiro
Abstract: Phytochemical analysis of Thevetia neriifolia seeds resulted in the isolation of one new (1 ) and 23 known (2 －24 ) cardenolide glycosides. The structure of 1 was determined based on one- and two-dimensional NMR spectroscopic analysis and acid hydrolytic cleavage reaction. The effect of the cytotoxic activity of 1 －24 on three human oral carcinoma cell lines was assessed. The cell lines included Ca9-22 human gingival carcinoma cells, HSC-2 human mouth carcinoma cells, HSC-4 human tongue carcinoma cells, and HGF human gingival fibroblast cells. The isolated compounds had a cytotoxic effect on the carcinoma cells with IC50 values ranging from 0.004 μM to 64.9 μM. The structure-activity relationship is also discussed. Graphical Abstract: